Multiscale Simulations for Electrochemical Devices - Asahi, Ryoji (Milton : Pan Stanford Publishing, 2019)
Environmental protection and sustainability are major concerns in today's world, and a reduction in CO2 emission and the implementation of clean energy are inevitable challenges for scientists and engineers today. The development of electrochemical devices, such as fuel cells, Li-ion batteries, and artificial photosynthesis, is vital for solving environmental problems. A practical device requires designing of materials and operational systems; however, a multidisciplinary subject covering microscopic physics and chemistry as well as macroscopic device properties is absent. In this situation, multiscale simulations play an important role. This book compiles and details cutting-edge research and development of atomistic, nanoscale, microscale, and macroscale computational modeling for various electrochemical devices, including hydrogen storage, Li-ion batteries, fuel cells, and artificial photocatalysis. The authors have been involved in the development of energy materials and devices for many years. In each chapter, after reviewing the calculation methods commonly used in the field, the authors focus on a specific computational approach that is applied to a realistic problem crucial for device improvement. They introduce the simulation technique not only as an analysis tool to explain experimental results but also as a design tool in the scale of interest. At the end of each chapter, a future perspective is added as a guide for the extension of research. Therefore, this book is suitable as a textbook or a reference on multiscale simulations and will appeal to anyone interested in learning practical simulations and applying them to problems in the development of frontier and futuristic electrochemical devices.
4.3 Electron Transfer Dynamics in Semiconductor/Metal-Complex for CO2 Reduction -- 4.3.1 Methodology -- 4.3.2 Results and Discussion -- 4.4 Summary and Future Scope -- 5: Large-Scale Simulations I: Methods and Applications for a Li-Ion Battery -- 5.1 Introduction -- 5.2 Method -- 5.2.1 Real-Space Grid Kohn-Sham DFT (RGDFT) Method [48] -- 5.2.2 Divide-and-Conquer-Type RGDFT Method [48] -- 5.2.3 Hybrid Quantum-Classical Simulation Method -- 5.2.3.1 Buffered cluster method -- 5.3 Applications
Description based upon print version of record.
5.3.1 Li-Ion Transfer through the Boundary between Solid/Electrolyte Interphase and Liquid Electrolyte [45]
OCLC-licensed vendor bibliographic record.
Keywords: Electrochemistry -- Simulation methods; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Mathematical Physics